Progress in complex Langevin simulations of full QCD at non-zero density - Sexty, Dénes (Nuclear physics. A, Nuclear and hadronic physics, 2014)
Progress in the application of the complex Langevin method to full QCD at non-zero chemical potential is reported. The method evades the sign problem which makes naive simulations at non-zero density impossible. The procedure ‘gauge cooling’ is used to stabilize the simulations at small enough lattice spacings. The method allows simulations also at high densities, all the way up to saturation. Simulations in a systematic hopping parameter expansion are also performed and good convergence is observed, validating the full as well as the expanded simulations.